Metamaterial interlayer hybrid structure and preparation method thereof
By using a combination of carbon fiber reinforced resin-based composite material layer, electromagnetic dielectric loss layer, metamaterial absorbing structure layer and impedance matching layer in the inter-layer hybrid structure, and using microwave heating technology, the traditional thermal curing molding process is solved. The problems of uneven temperature field and high residual stress have achieved efficient molding and structural-functional integration of aviation composite components.
Patent Information
- Application Number
- CN202411381783.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
In traditional thermal curing molding processes, the uneven distribution of temperature field and space-time distribution leads to desynchronization of curing, high residual stress, and poor interlayer interface bonding performance, which cannot meet the structural strength and bearing requirements of aviation aircraft.
The combination of carbon fiber reinforced resin-based composite material layer, electromagnetic dielectric loss layer, metamaterial absorbing structure layer and impedance matching layer is adopted to achieve rapid and efficient molding through microwave heating technology, reducing energy consumption and improving the overall mechanical properties of the structure.
It realizes rapid and efficient molding of mixed structures between metamaterial layers, reduces residual stress, improves the interface combination performance and overall load-bearing capacity of the material, meets the lightweight and high-reliability requirements of aviation composite components, and realizes structure-function Integrated molding manufacturing.
Smart Images

Figure CN119297606A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metamaterial interlayer hybrid structure and a preparation method thereof, and belongs to the technical field of functional materials. Background Art
[0002] As a type of structural absorbing material, the metamaterial interlayer hybrid structure has stronger designability and a wider application frequency band than traditional structural absorbing materials (hybrid fiber reinforced structure, silicon carbide fiber structure, sandwich structure, etc.). It takes into account both broadband absorbing function and structural bearing capacity, and has gradually become an important direction for the revolution of the new generation of military aircraft.
[0003] As an important component of the interlayer hybrid structure of metamaterials, metal electromagnetic metamaterials are characterized by light weight, thin thickness, strong designability and wider application frequency band. Without increasing the weight and thickness of the material, strong wave absorption performance within the design frequency band can be obtained by changing the structure of electromagnetic metamaterials. For example, the metamaterial structure in the disclosed patents CN112312754A and CN116315725A, however, the traditional thermal curing molding process used in the molding process has many curing defects and large structural deformation caused by the uneven temperature field, which greatly affects the aerodynamic performance and stealth function of the aircraft. At the same time, the structural design schemes in patents CN116454643B and CN112312754B mostly use magnetic materials with high dielectric constants (such as GXR-T101-C magnetic materials). Although the broadband wave absorption effect of the structure is well guaranteed, it cannot meet the structural strength and load-bearing requirements in the actual service environment of the aircraft. Therefore, the metamaterial interlayer hybrid structure based on high-strength, high-modulus carbon fiber reinforced composite materials, by introducing metamaterials and optimizing the design of its structural units, while ensuring that the metamaterial interlayer hybrid structure has broadband wave absorption and stealth functions, further increases the absorption peak at the industrial microwave heating frequency, making it possible for microwave heating technology to replace the traditional hot air circulation curing process and realize the rapid and efficient molding of the metamaterial interlayer hybrid structure. While reducing the residual stress of the component, the interface bonding performance and overall load-bearing capacity of the material are greatly improved, realizing the high-quality structure-function integrated molding and manufacturing of electromagnetic modulation components of aviation composite materials. Summary of the invention
[0004] In order to solve the problems of asynchronous curing, high residual stress level and poor interlayer interface bonding performance caused by the uneven temporal and spatial distribution of temperature field in the hot air circulation mode of traditional thermal curing molding process of metamaterial interlayer hybrid structure, a metamaterial interlayer hybrid structure and a preparation method thereof are provided, which changes the traditional manufacturing mode of metamaterial interlayer hybrid structure so that it can be cured and molded by microwave heating technology, greatly improving the overall mechanical properties of the structure and reducing energy consumption, while still meeting the special requirements of aviation load-bearing components for wide-band electromagnetic stealth function, thus realizing the structural-functional integrated molding and manufacturing of metamaterial interlayer hybrid structure.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows: A metamaterial interlayer hybrid structure comprises a carbon fiber reinforced resin-based composite material layer, an electromagnetic dielectric loss layer, a metamaterial absorbing structure layer and an impedance matching layer which are sequentially arranged from bottom to top.
[0006] Furthermore, the internal carbon fibers of the carbon fiber reinforced resin-based composite material layer have anisotropic conductivity, and after orthogonal multi-directional symmetrical ply design, the conductivity is 9000S / m~11000S / m; the thickness of the carbon fiber reinforced resin-based composite material layer is 0.5~3mm.
[0007] Furthermore, the electromagnetic dielectric loss layer is a glass fiber reinforced resin-based composite material, and the thickness of the electromagnetic dielectric loss layer is 0.5~3mm; the relative dielectric constant of the glass fiber reinforced resin-based composite material is 4.0~4.5, and the electric loss tangent is 0.02~0.03.
[0008] Furthermore, the metamaterial absorbing structure is composed of three layers of periodic electromagnetic structures with different unit sizes and shapes made of conductive metal materials, and the conductive metal material is one or more of copper, aluminum or silver; the unit shape of the periodic electromagnetic structure is a resonant ring composed of a cross, an arc, a square ring, an L-shape or a C-shape; the periodic distribution shape of the periodic electromagnetic structure is a square, and the periodic size is 8~15mm; the geometric shapes of the three layers of the metamaterial absorbing structure layer are similar, their sizes increase successively, and the laying angles differ by 90°.
[0009] Furthermore, the impedance matching layer is one or more of polytetrafluoroethylene, polymethacrylimide and polyvinyl chloride; the relative dielectric constant of the impedance matching layer is 2.1 for polytetrafluoroethylene, 1.107 for polymethacrylimide or 1.702 for polyvinyl chloride, and the electric loss tangent is 0.002 for polytetrafluoroethylene, 0.0145 for polymethacrylimide or 0.014 for polyvinyl chloride.
[0010] The method for preparing the above-mentioned metamaterial interlayer hybrid structure comprises the following steps: (1) Carbon fiber reinforced resin matrix composite material layer: According to the structural load requirements, the carbon fiber reinforced prepreg is stacked in an orthogonal multi-directional symmetrical layering method to form a carbon fiber reinforced prepreg laminate and placed at the bottom; (2) Electromagnetic dielectric loss layer: Cut the glass fiber reinforced prepreg according to the designed thickness and size, and stack them in an orthogonal multi-directional symmetrical layering manner to obtain a glass fiber reinforced prepreg laminate; (3) Metamaterial absorbing structure layer: According to the differences in metamaterial structure and size, magnetron sputtering, femtosecond laser or wire cutting are used to construct metamaterial absorbing structure layers of different shapes; (4) Adhesive films or resin coatings are bonded to the upper and lower surfaces of the glass fiber reinforced prepreg laminate obtained in step (2), and then placed on the carbon fiber reinforced prepreg laminate obtained in step (1), and the metamaterial absorbing structure layers of different shapes obtained in step (3) are sequentially laid on the upper surface of the glass fiber reinforced prepreg laminate; the glass fiber reinforced prepreg laminate and the metamaterial absorbing structure layers are alternately laid three times in a row, the thicknesses of different layers of the glass fiber reinforced prepreg laminate are different, and the size of the metamaterial absorbing structure layer unit increases from bottom to top.
[0011] (5) After adding a film or coating a resin on the upper surface of the metamaterial absorbing structure layer, the impedance matching layer is placed on the top to obtain a metamaterial interlayer hybrid structure preform; (6) The surface of the metamaterial interlayer hybrid structure preform obtained in step (5) is covered with a release film, a breathable felt, and a vacuum bag in sequence, and after being sealed and vacuumized, is placed in an industrial microwave heating furnace for microwave curing.
[0012] Furthermore, the microwave frequency of the microwave curing method is 2.45 GHz, and the temperature of the microwave curing is heated to 130° C. at a heating rate of 2° C. / min and kept warm for 120 minutes.
[0013] The beneficial effects of the present invention are: (1) The present invention proposes a metamaterial interlayer hybrid structure, which uses a carbon fiber reinforced composite material layer with good mechanical properties as a substrate. On this basis, microwave heating technology is used to achieve the overall solidification molding of the hybrid structure, making full use of the characteristics of microwave "in-volume" rapid heating. While avoiding the generation of temperature gradients inside the component and reducing residual stress, it improves the interface bonding strength between heterogeneous layers and fully guarantees the bearing performance of the component.
[0014] (2) The present invention proposes a metamaterial interlayer hybrid structure, which combines multiple layers of electromagnetic metamaterials with electromagnetic dielectric loss layers and impedance matching layers. Not only does the structure have a reflection coefficient of less than or equal to -10dB at the 2.45GHz industrial microwave heating frequency, but it also has good absorbing performance in the frequency range of 4-18GHz or even wider. The absorption rate in most frequency ranges is more than 90%, which can realize the functions of the metamaterial interlayer hybrid structure in low-frequency absorbing heating and high-frequency broadband stealth. At the same time, the metamaterial absorbing layer unit structure is simple and flexible in design, and has broad application prospects.
[0015] (3) The present invention proposes a metamaterial interlayer hybrid structure with structural and functional integration. The material is easily available and the microwave forming preparation process is novel, which can meet the stealth function requirements of lightweight and high reliability of aviation composite components.
[0016] (4) Compared with the prior art, the present invention changes the traditional molding mode of the hybrid structure between metamaterial layers, and provides design theory and technical support for the structural and functional integrated molding of composite material load-bearing components. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of a planar unit of the metamaterial absorbing structure layer of Example 1.
[0018] Figure 2 Schematic diagram of the three-dimensional structural unit of Example 1; wherein 1 is an impedance matching layer; 2, 4, and 6 are metamaterial absorbing structure layers; 3, 5, and 7 are electromagnetic dielectric loss layers; and 8 is a carbon fiber reinforced resin-based composite material layer.
[0019] Figure 3 It is a front view of Example 1; wherein 1 is an impedance matching layer; 2, 4, and 6 are metamaterial absorbing structure layers; 3, 5, and 7 are electromagnetic dielectric loss layers; and 8 is a carbon fiber reinforced resin-based composite material layer.
[0020] Figure 4 This is the reflection coefficient simulation result of Example 1.
[0021] Figure 5 This is the absorption rate simulation result of Example 1.
[0022] Figure 6 Schematic diagram of a planar unit of the metamaterial absorbing structure layer of Example 2.
[0023] Figure 7 Schematic diagram of the three-dimensional structural unit of Example 2.
[0024] Figure 8 This is the reflection coefficient simulation result of Example 2.
[0025] Fig. 9This is the absorption rate simulation result of Example 2.
[0026] Fig.10 Force-displacement curves when testing interface bonding performance using different curing processes.
[0027] Fig.11 Interlaminar shear strength of specimens prepared using different curing processes. DETAILED DESCRIPTION
[0028] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0029] Example 1 (1) Select 20 layers of unidirectional T800 carbon fiber reinforced prepreg and 45 layers of E-glass glass fiber prepreg, and cut them to a size of 130 mm × 130 mm (length × width).
[0030] (2) Take the 20 layers of unidirectional T800 carbon fiber reinforced prepreg cut in step (1) and press [0° / 90°] 10 The layers are stacked in an orthogonal multi-directional symmetrical manner to obtain a carbon fiber reinforced prepreg laminate placed on the bottom layer.
[0031] (3) Take 25 layers, 10 layers and 10 layers of E-glass fiber reinforced prepreg cut in step (1) respectively, and press [0° / 90°] 10 Three layers of glass fiber reinforced prepreg laminates are obtained by stacking in an orthogonal multi-directional symmetrical manner.
[0032] (4) Three layers of copper foil with a thickness of 0.02 mm and a size of 130 mm × 130 mm were cut, and three layers of metamaterial absorbing structure layers with the same number of arrays (10 × 10, a total of 100 units) were processed on the copper foil by femtosecond laser etching. The periodic unit size of the metamaterial absorbing structure layer is 13mm. The lower absorbing structure layer has two shapes of periodic electromagnetic structures, including a C-type open resonant ring with an outer diameter of 9.4mm and an inner diameter of 8.4mm, that is, the C-type ring line width is 0.5mm, and the opening size is 1.4mm, and the square ring outside the lower C-type open resonant ring has an outer diameter of 11.8mm and an inner diameter of 11.6mm, that is, the square ring line width is 0.2mm; the C-type open resonant ring in the middle metamaterial absorbing structure layer has an outer diameter of 8.4mm and an inner diameter of 7.6mm, that is, the C-type ring line width is 0.4mm, and the opening size is 2mm; the C-type open resonant ring in the upper metamaterial absorbing structure layer has an outer diameter of 6.4mm and an inner diameter of 5.8mm, that is, the C-type ring line width is 0.3mm, and the opening size is 1.6mm. The C-shaped ring is composed of two arcs and three rectangles. The opening of the resonant ring formed by the two C-shaped rings faces the diagonal of the square unit. The angles between different metamaterial absorbing structure layers differ by 90°, such as Figure 1 The planar unit structure of the metamaterial absorbing structure layer. It can be seen that there is a square ring and two C-shaped rings in the plane of the lower metamaterial absorbing structure layer. The square ring contains two C-shaped rings. The square ring is used to resonate at the industrial microwave frequency of 2.45GHz to achieve microwave heating, and the C-shaped open resonant rings between different metamaterial layers are nested with each other to achieve broadband absorption in the hybrid structure between metamaterial layers after curing.
[0033] (5) Select polytetrafluoroethylene with a thickness of 2.8 mm, a relative dielectric constant of 2.1, and an electric loss tangent of 0.002, and cut it to a size of 130 mm × 130 mm (length × width) as the polytetrafluoroethylene impedance matching layer.
[0034] (6) After coating the surface of the above-obtained material with resin, the material is layered in the following order (from bottom to top): 20 layers of carbon fiber reinforced prepreg laminates + 25 layers of glass fiber prepreg laminates + lower metamaterial absorbing structure + 10 layers of glass fiber reinforced prepreg laminates + middle metamaterial absorbing structure + 10 layers of glass fiber reinforced prepreg laminates + upper metamaterial absorbing structure + 1 layer of polytetrafluoroethylene impedance matching layer to obtain a metamaterial interlayer hybrid structure preform.
[0035] (7) The surface of the metamaterial interlayer hybrid structure preform obtained in step (6) is covered with a release film, a breathable felt, and a vacuum bag in sequence, and after sealing and vacuum treatment, it is placed in an industrial microwave heating furnace, and heated to 130° C. at a microwave frequency of 2.45 GHz at a heating rate of 2° C. / min and kept warm for 120 min to obtain Figure 2-3The metamaterial interlayer hybrid structure is shown in FIG., wherein the carbon fiber reinforced prepreg laminate is cured by microwave to obtain a carbon fiber reinforced resin-based composite material layer with an electrical conductivity of 10,000 S / m and a thickness of 2 mm; the glass fiber reinforced prepreg laminate is cured by microwave to obtain a glass fiber reinforced resin-based composite material as an electromagnetic dielectric loss layer with thicknesses of 2.5 mm, 1 mm, and 1 mm from bottom to top.
[0036] The finite element method is used to analyze the electromagnetic wave reflection and absorption characteristics of the periodic unit structure under normal electromagnetic wave incidence conditions. The corresponding reflection coefficient is as follows: Figure 4 As shown, the absorption rate is Figure 5 It can be seen that the structure has a strong wave absorption effect at the frequency of 2.45GHz, and the reflection coefficient is less than -5dB in the 4~7GHz frequency band, less than -8dB in the 7~11 frequency band, and less than -10dB in the 13.5~18GHz frequency band. It can be further calculated that the absorption rate in most of the 4~18GHz frequency band is higher than 90%, which has good broadband wave absorption and stealth function.
[0037] Example 2 Compared with Example 1, in this embodiment, in step (1), the shape of the open resonant ring of the metamaterial absorbing structure layer is changed to an arc shape, wherein the outer diameter of the lower arc-shaped resonant ring is 11 mm and the inner diameter is 10.2 mm, that is, the ring line width is 0.4 mm, and the opening center angle is 10°; the outer diameter of the square ring outside the lower arc-shaped open resonant ring is 12 mm and the inner diameter is 11.5 mm, that is, the square ring line width is 0.25 mm; the outer diameter of the middle arc-shaped resonant ring is 9.6 mm and the inner diameter is 8.8 mm, that is, the ring line width is 0.4 mm, and the opening center angle is 10°; the outer diameter of the upper resonant ring is 8 mm and the inner diameter is 7.2 mm, that is, the ring line width is 0.4 mm, and the opening center angle is 10°, so as to obtain Figure 6 The planar unit structure of the metamaterial absorbing structure layer has the same arrangement of the resonant ring as in Example 1; step (3) is changed to taking 20 layers, 10 layers and 15 layers of E-glass type glass fiber reinforced prepreg, respectively, with thicknesses of 2 mm, 1 mm and 1.5 mm from bottom to top; the remaining preparation steps and conditions are the same as in Example 1, and the metamaterial interlayer hybrid structure obtained by industrial microwave heating and curing has a three-dimensional structure as shown Figure 7 The finite element method is used to analyze the electromagnetic wave reflection and absorption characteristics of the periodic unit structure under normal electromagnetic wave incidence conditions. The reflection coefficient is shown in Figure 8 , the absorption rate is Fig. 9 , and also has good broadband electromagnetic stealth performance.
[0038] Comparative Example 1 The curing process of the metamaterial interlayer hybrid structure preform obtained in step (6) of Example 1 is changed to thermal curing in an oven, and the temperature is also heated to 130°C at a heating rate of 2°C / min and kept warm for 120 minutes. The preparation steps and conditions are the same as those of Example 1. This comparative example is used as a control group, and the interlayer interface bonding strength test is carried out on the components in Example 1 after being formed by microwave curing process to characterize their mechanical properties. Referring to the standard JC / T773-2010, the size of a single sample is determined to be 20mm×10mm (length×width), and a grinding wheel cutter is used to sample the metamaterial interlayer hybrid structure after curing and forming, and the number of samples for each layer is 5. The test process is carried out on a universal testing machine, the sample span-to-thickness ratio is set to 6, and the pressure head pressing speed is set to 1mm / min. The test results are as follows Fig.10 , 11 The results show that the hybrid structure of metamaterials cured by microwaves under the same process has a higher critical failure load, reflecting a better interlayer interface bonding performance. Its average interlayer shear strength increases by 10.74% compared with the thermally cured components.
[0039] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations on the implementation methods. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A metamaterial interlayer hybrid structure, characterized in that: The metamaterial interlayer hybrid structure comprises a carbon fiber reinforced resin-based composite material layer, an electromagnetic dielectric loss layer, a metamaterial absorbing structure layer and an impedance matching layer which are arranged in sequence from bottom to top.
2. The metamaterial interlayer hybrid structure according to claim 1, characterized in that: The internal carbon fibers of the carbon fiber reinforced resin-based composite material layer have anisotropic conductivity, and after orthogonal multi-directional symmetrical ply design, the conductivity is 9000S / m~11000S / m; the thickness of the carbon fiber reinforced resin-based composite material layer is 0.5~3mm.
3. The metamaterial interlayer hybrid structure according to claim 1, characterized in that: The electromagnetic dielectric loss layer is a glass fiber reinforced resin-based composite material, and the thickness of the electromagnetic dielectric loss layer is 0.5-3 mm; the relative dielectric constant of the glass fiber reinforced resin-based composite material is 4.0-4.5, and the electric loss tangent is 0.02-0.
03.
4. The metamaterial interlayer hybrid structure according to claim 1, characterized in that: The metamaterial absorbing structure layer is composed of three layers of periodic electromagnetic structures with different unit sizes and shapes made of conductive metal materials, and the conductive metal materials are one or more of copper, aluminum or silver; the unit shape of the periodic electromagnetic structure is a resonant ring composed of a cross, an arc, a square ring, an L-shape or a C-shape; the periodic distribution shape of the periodic electromagnetic structure is a square, and the periodic size is 8 to 15 mm; the three layers of the metamaterial absorbing structure layer have similar geometric shapes, their sizes increase successively, and the laying angles differ by 90°.
5. The metamaterial interlayer hybrid structure according to claim 1, characterized in that: The impedance matching layer is one or more of polytetrafluoroethylene, polymethacrylimide and polyvinyl chloride; the relative dielectric constant of the impedance matching layer is 2.1 for polytetrafluoroethylene, 1.107 for polymethacrylimide or 1.702 for polyvinyl chloride, and the electric loss tangent is 0.002 for polytetrafluoroethylene, 0.0145 for polymethacrylimide or 0.014 for polyvinyl chloride.
6. The method for preparing the metamaterial interlayer hybrid structure according to claim 1, characterized in that: The steps include: (1) Carbon fiber reinforced resin matrix composite material layer: According to the structural load requirements, the carbon fiber reinforced prepreg is stacked in an orthogonal multi-directional symmetrical layering manner to form a carbon fiber reinforced prepreg laminate and placed at the bottom; (2) Electromagnetic dielectric loss layer: Cut the glass fiber reinforced prepreg according to the designed thickness and size, and stack them in an orthogonal multi-directional symmetrical layering manner to obtain a glass fiber reinforced prepreg laminate; (3) Metamaterial absorbing structure layer: According to the differences in metamaterial structure and size, magnetron sputtering, femtosecond laser etching or wire cutting are used to construct metamaterial absorbing structure layers of different shapes; (4) Adhesive films or resin coatings are applied to the upper and lower surfaces of the glass fiber reinforced prepreg laminate obtained in step (2), and then the laminate is placed on the carbon fiber reinforced prepreg laminate obtained in step (1), and the metamaterial absorbing structure layers of different shapes obtained in step (3) are sequentially laid on the upper surface of the glass fiber reinforced prepreg laminate; the glass fiber reinforced prepreg laminate and the metamaterial absorbing structure layers are alternately laid three times in a row, the thicknesses of different layers of the glass fiber reinforced prepreg laminate are different, and the size of the metamaterial absorbing structure layer unit decreases from bottom to top; (5) After adding a film or coating a resin on the upper surface of the metamaterial absorbing structure layer, the impedance matching layer is placed on the top to obtain a metamaterial interlayer hybrid structure preform; (6) The surface of the metamaterial interlayer hybrid structure preform obtained in step (5) is covered with a release film, a breathable felt, and a vacuum bag in sequence, and after being sealed and vacuumized, is placed in an industrial microwave heating furnace for microwave curing.
7. The preparation method according to claim 6, characterized in that: The microwave frequency of the microwave curing method is 2.45 GHz, and the temperature of the microwave curing is heated to 130° C. at a heating rate of 2° C. / min and kept warm for 120 minutes.
Citation Information
Patent Citations
Structural composite wave-absorbing material and preparation method thereof
CN112312754A
A structural composite microwave absorbing material and its preparation method
CN112312754B
Wave-absorbing and wave-transmitting integrated metamaterial and preparation method thereof
CN116315725A
A low-frequency broadband absorbing material
CN116454643B
Cited By
Reconfigurable metamaterial interlayer hybrid structure based on PIN diode and preparation method thereof
CN122576699A